Cardiac deceleration capacity and acceleration capacity have diagnostic value in patients with vasovagal syncope regardless of age - Wang, Jijing; Xu, Jinyi; Qiu, Yanyan; Yang, Ruike; Wang, Wentao; Gao, Chuanyu (Frontiers in Cardiovascular Medicine, 2024)
BackgroundDeceleration capacity (DC) and acceleration capacity (AC) are used to characterize autonomic regulation. The purpose of this study was to evaluate the autonomic nervous function in patients with vasovagal syncope (VVS) and to evaluate the diagnostic value of DC and AC for VVS.MethodsA total of 94 consecutive patients with VVS [51.0 (38.0–60.0) years; 48 males] and 76 healthy subjects [53.0 (44.3–62.8) years; 46 males] were recruited as controls. The study compared DC, AC, and heart rate variability (HRV) in 24-h ECG, echocardiogram, and biochemical examinations between the two groups.ResultsDC was significantly higher (9.3 ± 2.1 vs. 7.4 ± 1.4 ms, p < .001) and AC was lower (−9.3 ± 2.1 vs. −7.3 ± 1.3 ms, p < .001) in the syncope group compared to the control group. HRV indicators were higher in the syncope group. In multivariable analyses, DC [odds ratio = 1.746 (95% CI, 1.389–2.195); p < .001], AC [odds ratio = 0.553 (95% CI, 0.435–0.702); p < .001] were independently associated with syncope. Mean HR was associated with syncope only in patients <60 years of age. Receiver operating characteristics (ROC) curves showed areas under curve (AUC) of DC/AC for predicting syncope are 0.755/0.765 with sensitivity of 56.4%/60.6% and specificity of 93.4%/88.2%.ConclusionPatients with VVS exhibit higher DC and lower AC. Both DC and AC are independently correlated with syncope. A DC value >9.0 ms and an AC value −9.0 ms could potentially be valuable indicators for monitoring cardiac autonomic nervous dysfunction.